2013
DOI: 10.12669/pjms.292.3148
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of migraine in patients with allergic rhinitis

Abstract: Objectives: Allergic rhinitis (AR) is an IgE mediated disease which is released by activation of mast cells and basophils, and often leads to sinus headache. Histamine which is the key mediator in the pathogenesis of AR, also plays an important role in the pathogenesis of migraine with nitric oxide (NO). Aim of our study was to investigate the frequency of migraine in patients with AR. Methodology: Headache assessment and neurological examination was performed on patients diagnosed as AR in the outpatient ear … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…reported migraine in 34% of AR patients and in 4% of non‐AR controls. Similarly, Ozturk et al . and Saberi et al .…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…reported migraine in 34% of AR patients and in 4% of non‐AR controls. Similarly, Ozturk et al . and Saberi et al .…”
Section: Discussionmentioning
confidence: 64%
“…However, these were hospital‐based and cross‐sectional studies with limited numbers of patients, where no causal relationship was confirmed. In addition, these studies essentially focused on adult patients, and the exact incidence rate and relative risks of migraine in children with AR is not clear. Our results suggest that children with AR are more likely to develop migraine regardless of sex, age, and urbanization of living area.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Allergic rhinitis is defined as a chronic inflammatory disease of the upper airway caused by an IgE-mediated inflammatory response of the nasal mucous membranes after exposure to inhaled allergens. It is characterized by the symptoms of rhinorrhea (anterior or posterior nasal drainage), nasal congestion, sneezing, and nasal itching (Table 1 ) [ 29 •], and it often leads to sinus headache [ 36 ]. Allergic rhinitis may be classified according to the temporal pattern of exposure to the allergen: for example, seasonal allergic rhinitis, in which the inflammatory response is related to seasonal aeroallergens (e.g., tree, grass, weed pollens), and perennial allergic rhinitis, in which the response is related to year-round environmental aeroallergens (e.g., dust mites, mold, pet danders, or certain occupational allergens).…”
Section: Diagnostic Criteria Of Diseases Associated With Sinus Headacmentioning
confidence: 99%
“…Certainly, it is well established that allergens can activate trigeminal nociceptors by releasing inflammatory chemicals from dural mast cells, triggering a migraine attack [ 73 – 75 ]. Evidence also exists that histamine may induce migraine attacks by increasing the level of nitric oxide (NO) [ 36 ], which is believed to promote migraine attacks through its vasodilator effects via H1 and H2 receptors; this is another inflammatory mediator found in both allergic rhinitis and migraine [ 57 , 76 , 77 ]. Inflammation plays an important role in the complex pathogenesis of migraine as well as of allergic rhinitis [ 58 , 78 ].…”
Section: Comorbidity and Pathophysiologymentioning
confidence: 99%